2016
DOI: 10.14411/fp.2016.008
|View full text |Cite
|
Sign up to set email alerts
|

A synoptic review of Promonobothrium Mackiewicz, 1968 (Cestoda: Caryophyllidea), parasites of suckers (Catostomidae) in North America, with description of two new species

Abstract: Monozoic cestodes of the recently amended genus Promonobothrium Mackiewicz, 1968 (Cestoda: Caryophyllidea), parasites of suckers (Cypriniformes: Catostomidae) in North America, are reviewed, with information on their host specificity, distribution and data on the scolex morphology of seven species studied for the first time using scanning electron microscopy (SEM). Evaluation of type and voucher specimens from museum collections and newly collected material of most species indicated the following valid nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Recent studies on North American caryophyllideans have revealed high diversity of these tapeworms, previously only partly described. Two new genera were erected and nine new species of the genera Biacetabulum Hunter, 1927, Promonobothrium Mackiewicz, 1968 and Isoglaridacris Mackiewicz, 1965 described [ 37 , 39 , 40 , 49 , 54 56 ]. In the present paper, three new species of the enigmatic Archigetes are described from catostomid fishes from the southern United States (USA).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on North American caryophyllideans have revealed high diversity of these tapeworms, previously only partly described. Two new genera were erected and nine new species of the genera Biacetabulum Hunter, 1927, Promonobothrium Mackiewicz, 1968 and Isoglaridacris Mackiewicz, 1965 described [ 37 , 39 , 40 , 49 , 54 56 ]. In the present paper, three new species of the enigmatic Archigetes are described from catostomid fishes from the southern United States (USA).…”
Section: Introductionmentioning
confidence: 99%
“…To provide a robust taxonomic baseline for future ecological, evolutionary and biogeographical studies, individual genera of North American caryophyllideans are being revised, based on a critical examination of type material and newly collected and properly processed specimens, including hologenophores, from North American catostomids (Scholz et al, 2015;Oros et al, 2016Oros et al, , 2018. One of the more species-rich genera of caryophyllideans is Biacetabulum Hunter, 1927 with 10 recognised species (Scholz and Oros, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, specimens of caryophyllidean tapeworms fixed using a standardized method (see Oros et al, 2010) were freshly collected from a variety of fish hosts, including suckers (Catostomidae), in Canada and the USA. This new material has enabled us to critically examine the validity of several genera of North American caryophyllideans (Scholz et al, 2015;Oros et al, 2016Oros et al, , 2018. Furthermore, molecular data were generated for specimens of Biacetabulum from different species of redhorses (Moxostoma spp.)…”
Section: Introductionmentioning
confidence: 99%
“…tornou-se frequente nas descrições e revisões taxonômicas para o grupo (e.g. SCHOLZ; DRÁBEK;HANZELOVÁ, 1998;CAIRA;CARPENTER, 2006;MENORET;IVANOV, 2014;OROS et al, 2016), principalmente devido ao desenvolvimento da tecnologia dos microscópios que permitiram que espécimes diminutos também fossem analisados. Para táxons como Lecanicephalidea, Rhinebothriidea, Trypanorhyncha e os grupos dentro de Tetraphyllidea, adisponibilidade de dados acerca de microtríquias é vasta, com diversos morfotipos destas estruturas registrados para estes parasitas (e. g. PALM, 2004; JENSEN, 2005; MALEK; CAIRA; HASELI, 2010; RUHNKE; CAIRA; COX, 2015).…”
unclassified